PENINGKATAN KEMAMPUAN BERBICARA MELALUI METODE BERCERITA MENGGUNAKAN CERITA BERGAMBAR DI TK NURUL IMAN UJAN RINTIS - Jakranah Jakranah; Samsul Mujtahidin (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
The purpose of this study was to investigate how storytelling using picture storytelling can improve children's speaking skills in a kindergarten of Nurul Iman Ujan Rinti. This study uses a qualitative approach with a classroom action research design. The research environment was in a kindergarten of Nurul Iman Ujan Rinti, and the research subjects were 2 teachers and 15 children in Group A. The action plan provided was the use of illustrated stories to improve children's speaking ability which was carried out for 2 cycles consisting of planning, implementing, observation and reflection, where each cycle consists of two meetings. Data collection techniques through observation and documentation are processed qualitatively. The results of the study show that through the storytelling method using picture stories, children's speaking ability can improve. This can be seen in cycle I which shows that most of the children are in the category of starting to develop, then experiencing an increase in cycle II by being in the category of developing according to expectations and developing very well. The indicators of speaking ability are 1) the child's ability to answer questions, 2) the child's ability to tell about experiences related to the pictures that have been provided.